The Role of Environmental Education and the Utilization of Recycled Waste in Improving the Economic Welfare of the Community in Babakan Village, Sukabumi City - Anggiana Putri Lestari; Nurna Sri Wahyuni; ⁠Rahayu Anggraini; Resy Sofia; Safana Syawal; Vina Siti Salmah Khoirunnis; Windy Novalianti; Zia Srimulani; Tuti Setiatin; Ebah Suaebah (Siber Nusantara of Community Service Review, 2026)
Waste problems are an increasingly complex environmental issue, especially in residential areas that do not have an optimal management system, such as in Babakan Village. Low public awareness in sorting and utilizing waste leads to increased environmental pollution as well as loss of economic potential from the waste produced. Therefore, this activity aims to analyze the role of environmental education and the use of recycled waste in improving the economic welfare of the community. The method used is a community empowerment approach through four stages, namely planning, socialization and education, training and practice, and monitoring and evaluation. The results of the activity show an increase in community knowledge, awareness, and skills in managing waste, especially through the application of the 3R (Reduce, Reuse, Recycle) concept. The community is starting to be able to process inorganic waste into products of economic value, such as handicrafts, and utilize organic waste into compost. In addition, there has been an increase in community participation in community-based waste management activities. However, there are still obstacles in the sustainability of the program, especially related to the consistency of participation and marketing development of recycled products. Overall, this activity shows that environmental education combined with the direct practice of using recycled waste is effective in encouraging changes in community behavior while opening up opportunities to increase income. This program has the potential to become a model of sustainable community empowerment in supporting environmental sustainability and economic welfare